(untitled) (Latakia University Journal -Engineering Sciences Series, 2019)
FLAME HARDENING is a heat-treating process in which a thin surface shell of a steel part is heated rapidly to a temperature above the critical point of the steel. After the grain structure of the shell has become austenitic, the part is quickly quenched, transforming the austenite to martensite while leaving the core of the part in its original state. To achieve hardness, the steel must be cooled rapidly so that it bypasses the first two transformation phases and transforms directly from austenite to martensite. Flame hardening employs direct impingement of a high-temperature flame or high-velocity combustion product gases. Depths of hardening from about 0.8 to 6.4 mm or more can be obtained, depending on the fuels used, the design of the flame head, the duration of heating, the hardenability of the work material, and the quenching medium and method of quenching used. Although flame hardening is mainly used to develop high levels of hardness for wear resistance, the process also improves bending and torsional strength and fatigue life In this research we study the effect of flame hardening and prior soft annealing on 0.6% carbon steel microstructure, hardness and hardness depth. يهدف هذا البحث إلى دراسة تأثير التقسية السطحية باللهب على القساوة والبنية المجهرية للفولاذ الكربوني 0.6%) كربون) ودراسة تأثير تخمير التكوير السابق للتقسية على القساوة والبنية المجهرية للفولاذ الكربوني كذلك. حيث تمت دراسة التغيرات الحاصلة على البنية البلورية والقساوة السطحية وعمق التقسية مع وبدون تخمير التكوير لمعرفة التغيرات الحاصلة ومقارنة النتائج. فقد بين البحث تأثير التقسية السطحية باللهب على كل من البنية البلورية والقساوة السطحية وعمق التقسية للفولاذ المستخدم في البحث، للحصول على مزيج فريد من الخواص، من سطح قاسي مقاوم للاحتكاك وقلب مرن مقاوم للصدم. كما أشار إلى تحسن هذه الخواص عند إجراء عملية تخمير التكوير للفولاذ قبل عملية التقسية المذكورة.